Surgical treatment of biatrial myxoma - A. S. Ivanov (Vestnik Transplantologii i Iskusstvennyh Organov, 2022)
Cardiac myxoma is a primary tumor histologically formed by multipotent subendocardial mesenchymal cells. Myxomas account for approximately 50% of all cardiac tumors in adults. Myxomas are most commonly located in the left atrium. Very rarely, myxomas can be located in several heart chambers. Only about 100 cases of patients with myxomatous lesions of both atria have been described in the literature. In this paper, we present a successful clinical case of a young patient with biatrial myxomas.